1995
DOI: 10.5032/jae.1995.01038
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Minority And Non-Minority Students To Enroll In An Introductory Agriscience Course In Texas

Abstract: The authors investigated attitudes toward agriculture of minority and non-minority students to identify reasons for enrolling and perceived enrollment barriers. A stratified random sample of all students enrolled in two introductory agriscience courses in 60 agriscience programs was selected and surveyed using a five-part questionnaire. The major findings and conclusions were that: 1) the majority of students and teachers were white males; 2) minority students, especially minority females, were underrepresente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 10 publications
3
40
1
Order By: Relevance
“…Past studies have indicated numerous factors influencing student enrollment behaviors including parents, friends, and significant others (Luft & Geise, 1991;Marshall, Herring, & Briers, 1992;Reis & Kahler, 1997); circumstantial/disavowance reasons (Marshall, Herring, & Briers, 1992); interests (Connors, Moore, & Elliot, 1989;Marshall, Herring, & Briers, 1992); image, future value, and perceptions of agriculture (Hoover & Scanlon, 1991;Talbert & Larke, 1995); and career and educational preparation, developmental skills, academic enhancement, response to social pressure, and participation in activity enhanced learning (Sutphin & Newsom-Stewart, 1995). Although these studies have identified numerous factors influencing enrollment in secondary programs of agriculture, there has been limited research efforts focused on students enrolled in secondary agricultural programs within urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have indicated numerous factors influencing student enrollment behaviors including parents, friends, and significant others (Luft & Geise, 1991;Marshall, Herring, & Briers, 1992;Reis & Kahler, 1997); circumstantial/disavowance reasons (Marshall, Herring, & Briers, 1992); interests (Connors, Moore, & Elliot, 1989;Marshall, Herring, & Briers, 1992); image, future value, and perceptions of agriculture (Hoover & Scanlon, 1991;Talbert & Larke, 1995); and career and educational preparation, developmental skills, academic enhancement, response to social pressure, and participation in activity enhanced learning (Sutphin & Newsom-Stewart, 1995). Although these studies have identified numerous factors influencing enrollment in secondary programs of agriculture, there has been limited research efforts focused on students enrolled in secondary agricultural programs within urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…The rural organizational culture (Martin & Kitchel, 2013) presented at the National FFA Convention was not a major barrier. They did not express negative perceptions of FFA members (Hoover & Scanlon, 1991;Phelps, Henry, & Bird, 2012) and agriculture (Jones & Bowen, 1998;Talbert & Larke, 1995). Some members even tried to tie the rural messages to their urban context.…”
Section: Research Question Three: Negotiating Connections To Ffa Aftementioning
confidence: 99%
“…The ruralness and mainly white FFA members of the convention created a sense of curiosity, nervousness, and wanting among some members. However, they did not talk about negative stereotypes of rural FFA members (Hoover & Scanlon, 1991;Phelps, Henry, & Bird, 2012) and agriculture (Jones & Bowen, 1998;Talbert & Larke, 1995;Warren & Alston, 2007). Some of the other Belmont FFA members were not as enthusiastic about the rural themes.…”
Section: Research Question Two: Members Experiences At Conventionmentioning
confidence: 99%
“…Attitudinal barriers include minority students' negative perceptions of agriculture and agricultural programs (Bowen, 1993;Bowen, Bowen, & Heinsohn, 1997;Myers, Breja, & Dyer, 2004;Sutphin & Newsom-Stewart, 1995;Talbert & Larke, 1995;Talbert, Larke, & Jones, 1999), misperceptions of career paths and/or availability (Bowen et al; Sutphin & Newsom-Stewart), and a view that the profession is made up of, and for, White men (Bowen et al; Sutphin & Newsom-Stewart).…”
Section: Introductionmentioning
confidence: 99%
“…95). Agricultural education researchers have stated that peers can influence one's attitudes about careers and recommend workshops or seminars during elementary and secondary education to introduce minority students to agriculture and agricultural programs (Bowen et al, 1997;Talbert & Larke, 1995).…”
Section: Introductionmentioning
confidence: 99%